2021
DOI: 10.1016/j.marpolbul.2021.112131
|View full text |Cite
|
Sign up to set email alerts
|

An appraisal of systematic conservation planning for Pacific Ocean Tropical Islands coastal environments

Abstract: Highlights► Systematic conservation planning in the Pacific Ocean islands is growing.► 34 case studies from 2000 to 2020 are reviewed.► Melanesia (Fiji) is the most studied.► Seven technical and thematical priorities or missed opportunities are highlighted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 133 publications
(232 reference statements)
1
4
0
1
Order By: Relevance
“…With more diverse criteria than most conservation plans for wild species, our study is consistent with the recommendations by André et al (2021a) for the Pacific Islands. These authors identified a lack of planning studies taking into consideration local specific activities, such as black pearl farming, and invertebrate resources.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…With more diverse criteria than most conservation plans for wild species, our study is consistent with the recommendations by André et al (2021a) for the Pacific Islands. These authors identified a lack of planning studies taking into consideration local specific activities, such as black pearl farming, and invertebrate resources.…”
Section: Discussionsupporting
confidence: 84%
“…To our knowledge, the use of a systematic spatial prioritization toolbox for such a purpose has never been reported. This study constitutes an original contribution to the panel of management or conservation questions addressed by the general field of systematic conservation planning in tropical island environments (André et al, 2021a), because it integrates pearl farming related issues for the first time.…”
Section: Discussionmentioning
confidence: 99%
“…Al mismo tiempo, para conservar la biodiversidad en la actualidad se están empleando herramientas integradoras, como la planificación sistemática de la conservación (PSC), que en poco tiempo se ha convertido en un estándar para diseñar y evaluar iniciativas de nuevas áreas de conservación [22], ya que es un proceso de apoyo [23], que ofrece conceptos y cajas de herramientas para tomar decisiones espaciales sobre dónde enfocar los esfuerzos y al mismo tiempo, minimizar una variedad de costos para las partes interesadas [24,25]. Agregando a lo anterior, el empleo de sistemas de información geográfica (SIG), como herramienta de planificación para salvaguardar la biodiversidad permite almacenar, analizar y procesar la información desde múltiples dimensiones [26], siendo en ocasiones el único método que proporciona soluciones específicas a problemas que no podrían resolverse con métodos convencionales [27], por tanto, se recomiendan a los tomadores de decisiones que planifican de forma remota la conservación y la gestión [28].…”
Section: Introductionunclassified
“…These costs translate the loss of access to fishing grounds selected for conservation and closed to extractive activities. Many marine SCP examples have emerged in the past decade, using simple to complex scenarios in terms of scales, objectives and cost functions (Ban and Klein, 2009;Magris et al, 2014;Álvarez-Romero et al, 2018, André et al, 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Often, biodiversity conservation plans are in conflict with human activities, and SCP is increasingly used in these conflicting areas to help finding solutions. However, accessing accurate and reliable data represents a true challenge for SCP, particularly on opportunity costs to fishers Deas et al, 2014, André et al, 2021. Indeed, apart from some exceptions, there is a substantial lack of available and updated knowledge on artisanal fisheries worldwide (Jacquet and Pauly, 2008;FAO, 2018) despite they directly employ and support food security for millions of people (FAO, 2017).…”
Section: Introductionmentioning
confidence: 99%